-(6x-1)=0

Simple and best practice solution for -(6x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(6x-1)=0 equation:



-(6x-1)=0
We get rid of parentheses
-6x+1=0
We move all terms containing x to the left, all other terms to the right
-6x=-1
x=-1/-6
x=1/6

See similar equations:

| 11-1/2y=3+6y | | |3n-4|=-1 | | 2u^2-5u-18=0 | | -6x+1=14x5 | | 12=-3(2x+2)+7x | | |3n-4|=1 | | 90=12x+42 | | 3x/4-7/5=2x/10 | | 0.1x-0.6x-14=1 | | -3a+3+4a=10-21 | | x(4)=2x | | 6x-10=4x+22 | | 2+5.7t-4.9t^2=0 | | 2=​2/m−7 | | 1.5t^2-24t=0 | | x+5=-81 | | 4f-16+2f=3f+11 | | x+2(x-7)=3x-7 | | 4r=21+2.50r | | (4x+9)+(4x+8)+(4x)=(4x)+4x)+(5x+6) | | F(x)=5/6x-15 | | 3z+15=48 | | 8x-2(3x-5)=24 | | 8(5x-3=6(-3x-4) | | -1/8c=-5/4 | | 2r-3/5=3 | | 3(x-4)=2x=6 | | 6x-12=18-8x | | (4x+9)+(4x+8)+(4x)=(4x)=(4x)+(5x+6) | | 0.7x-0.4(50+x)=-0.1(50) | | 3x+4(x+6)=6x-4x+x | | 4x+8=-4(2x-7)+2x |

Equations solver categories